Ill-treatment in the Chilean prison system – an analysis of reports presented by the National Institute of Human Rights (INDH) and their handling by the legal actors - Stippel, Jörg Alfred; Sanhueza, Rodrigo; Vergara Cisternas, Luis (Torture Journal, 2024)
Prisons in Latin America are often described as violent and lawless places. In this context, we analyse the Chilean case. We want to find out how complaints of torture and ill-treatment are investigated if the victim is a person deprived of liberty? Our hypothesis is that the response to the phenomenon, both in the prosecution of the perpetrators and in the protection of its victims, does not take into consideration the guidelines established in international standards, especially those contained in the Istanbul Protocol. To this end, we analyse a total of 124 complaints of torture or ill-treatment filed by the Chilean National Human Rights Institute (INDH). This information was then used to research the processing of these cases in the virtual portal of the Chilean Judiciary. In a next step we created a database that contains different information extracted from the electronic case files. This is the source for the quantitative analysis. For the qualitative part of our study, we describe the facts contained in the complaints and document the way they were handled. The findings confirm our hypothesis. An excessive amount of time elapses between the alleged torture or mistreatment, the filing of complaints, the use of protective measures and the termination of the cases. There are serious deficiencies in the investigations carried out by the Public Prosecutor's Office. Therefore, most of the complaints are not clarified and end up being shelved sooner or later. We conclude that, both the actions of the judges and the prosecutors in the processing of the complaints, make it clear that when it comes to investigating acts of torture or ill-treatment inside Chilean prisons, the standards of the Istanbul Protocol are not met.